Are female top managers really paid less? - Geiler, Philipp; Renneboog, Luc (Journal of Corporate Finance, 2015)
We study the gender pay gap for all top managers (CEO and executive directors) of listed UK companies and find mixed evidence: female CEOs do not face a pay gap, but the other female executive directors (e.g. CFO, COO, Deputy CEO) are discriminated against (while controlling for position, tenure, age, industry, time period, marital status, and parenthood). These female top managers earn about 23% less than their male counterparts, which amounts to £1.3million over a five-year period (their average tenure as an executive at the board level). The gender pay gap is lower for managers in firms with female non-executive directors on the board. Also, female managers working in “male” industries experience a smaller pay gap. When remuneration contracting occurs with the help of top remuneration consultants, we note that the total remuneration offered to top managers is higher but the pay gap for executive directors still remains (but not for the CEO). The gender pay gap increases in case of marriage and parenthood.